Pengaruh gaya kepemimpinan dan system Pengendalian intern terhadap anggaran berbasis Kinerja pada blu universitas mataram - Sri Wahyulina; Biana Adha Inapty (Universitas Mercu Buana Yogyakarta, 2015)
This study aimed to examine the influence of leadership style and internal control system to the implementation of Performance-based budgeting. The study population is an administrative officer who works at the University BLU environment. The sampling technique in this research using purposive sampling method, which is only the employees associated with the implementation of performance-based budgeting, starting from preparation to budget accountability. Data obtained by distributing questionnaires to 50 respondents who fit into the criteria of the samples. Analysis of data using Multiple Linear Regression Analysis. The results showed that the style of leadership and internal control system has positive influence on the implementation of performance-based budgeting. The better the leadership style accepted by subordinates, and the better the internal control system implemented in the management of financial institutions, the better the application of performance-based budgeting at the University of Mataram BLU. The implications of this study can explain the importance of leadership style factors, and internal control system in supporting the implementation of performance-based budgeting. As explained in the Theory X and Y.Keywords : performance-based budgeting, leadership style, internal control system, Public service agency.